9m+26=5m+3

Simple and best practice solution for 9m+26=5m+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9m+26=5m+3 equation:



9m+26=5m+3
We move all terms to the left:
9m+26-(5m+3)=0
We get rid of parentheses
9m-5m-3+26=0
We add all the numbers together, and all the variables
4m+23=0
We move all terms containing m to the left, all other terms to the right
4m=-23
m=-23/4
m=-5+3/4

You can always share this solution

See similar equations:

| x^2+12x-51=0 | | 2x-16=x+44 | | 3y+4(7-2y)-6(y+14)=-1-(y+5) | | (6y•2)=-5•6y-6+174 | | -(1-5x)+6=10+5x | | F4(w-5)-4=-3(-7w+4)-7w | | 11x-5=8x-6 | | -4w+10=-2(w-7) | | 3/10=10x | | 4(w-4)-8w=-8 | | 4(5+8d)D=84 | | 2-6(1-x)+x=4(2x-1)-x | | 17x-3=-43 | | 80-2x=30x= | | (10x+6)(6x+4)=90 | | (a+2)*(a+3)=3 | | -6=(5x-12)/3 | | 2a+1=10 | | (2x-1)(x+17)=0 | | 1+7p+p=1 | | 3(m+5)=12 | | 10(z+1)-5(z-2)=2(z-2)+2(z-1) | | (4a-1)=-23- | | 2(m-1)=-5(4m-m) | | -6w-14=8(w-7) | | 3(2x-3)-3=3(x-2)+9 | | X-0,15x=4800 | | (x-10)=-99 | | 1.5=1.2y=5.7 | | 2=10-3(x+7)+5(1-x)+6x | | X=7x-23 | | 4b÷8=20b= |

Equations solver categories